Revitalizing Democracy and Governance in post COVID-19 Pandemic: Bangladesh perspective - Arifa, Nazia (Asian Studies, 2023)
financial glitches, as well as political upheavals, in addition to substantial public health disputes. Public safety concerns have clashed with democratic civic norms and expectations as well as basic rights because of this uncertain pandemic scenario, which has caused unsteadiness in Bangladesh's social structure, governance, and political system. To recuperate miserable circumstances of Bangladesh and counteract the effects of COVID-19, it is essential to resuscitate democracy and governance after pandemic era. The aim of this research is to investigate approaches that will reenergize democracy and governance of Bangladesh after pandemic. The study was conducted using a qualitative research methodology. The paper examines COVID-19's negative impacts as well as presents proposals for establishing good governance and accountable institutions, efficient leadership and management, implementing USAID program and the G&I Umbrella Program of the Work Bank, efficient leadership and management, free and fair elections, active local government, civil society, and civic engagement in public decision-making for recovering Bangladesh's damaged democracy and governance in the wake of the catastrophe.